Capital humano, social e intelectual en la era COVID-19: establecimiento de la agenda, encuadre, plausibilidad y verificabilidad en los repositorios - García Lirios, Cruz (Pontificia Universidad Católica del Perú, 2021)
The health and economic crisis caused by the SARS CoV-2 coronavirus and the COVID-19 disease has accelerated the emergence of an informational economy focused on the use of electronic networks. The impact of this scenario on education led to the transition from the traditional classroom to the electronic whiteboard. The objective of the present work is to analyze the relationships between human, social, and intellectual capital. A model showing the prevalence of human capital creation as indicated by data processing in the virtual class-room and self-management of knowledge was established.

La crisis sanitaria y económica provocada por el coronavirus SARS CoV-2 y la enfermedad COVID-19 han acelerado el surgimiento de una economía de la información centrada en el uso de redes electrónicas. El impacto de este escenario en la educación propició la transición del aula tradicional a la pizarra electrónica. El objetivo del presente trabajo fue analizar las relaciones entre capital humano, social e intelectual. Se estableció un modelo en el que se aprecia el predominio de la formación de capital humano indicado por el procesamiento de datos en el aula virtual y la autogestión del conocimiento.
Human, Social, and Intellectual Capital in the COVID-19 Era: Establishing the Agenda. Framing, Plausibility, and Verifiability in the Repositories
Keywords: Heads of household; Social work; Entrepreneurship; Specification; Mode; Jefes de hogar; Trabajo social; Emprendimiento; Especificación; Modo; https://purl.org/pe-repo/ocde/ford#5.09.01